2016
DOI: 10.1186/s40064-016-2606-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated C-reactive protein is associated with disease progression in patients with mild Crohn’s disease

Abstract: BackgroundFew studies have been conducted on the progression of mild Crohn’s disease (CD). We aimed to investigate the natural course in mild CD patients with or without bowel damage, to identify predictors of bowel resection and to calculate the requirement for rescue medication.MethodsA total of 104 patients with mild activity (150 < CDAI < 220) with or without bowel damage were identified from among 1050 CD patients between January 2008 and May 2014. Univariate and multivariate analysis was used to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These different correlations may be due to the poor agreement among clinical, endoscopic and histological activity in IBD patients [27]. Numerous studies have shown the correlation of disease activity with inflammatory markers was much stronger for CD than for UC [14,28,29]. Similarly, we found ACK1 expression correlated less well with clinical activity in UC relative to CD.…”
Section: Discussionmentioning
confidence: 50%
“…These different correlations may be due to the poor agreement among clinical, endoscopic and histological activity in IBD patients [27]. Numerous studies have shown the correlation of disease activity with inflammatory markers was much stronger for CD than for UC [14,28,29]. Similarly, we found ACK1 expression correlated less well with clinical activity in UC relative to CD.…”
Section: Discussionmentioning
confidence: 50%
“…[ 15 ] According to previous reports, increased CRP levels in patients with CD in clinical remission is associated with increased subsequent disease activity, and a significantly increased need for hospitalization and surgical treatment related to CD. [ 16 , 17 ] The CRP level reflects the current condition of CD, and has utility as a biomarker predicting the subsequent prognosis. The present study showed significant correlations between the CRP level and the CDAI and IOIBD in patients with CD without enterostomy.…”
Section: Discussionmentioning
confidence: 99%